Effect of Integrated sessions of anatomy and physiology on academic performance: A pilot study - Haque, Ayesha; Naveed, Ayesha; Ashraf, Muhammad Imran; Rana, Shazana; Mirza, Tayyeba Iftikhar; Ghassan, Ayesha (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To conduct integrated sessions of anatomy and physiology for ascending tracts and determine its effect on academic performance and determine perceptions of the students regarding its effectiveness. Methods: Using nonprobability convenience sampling, fifty-three students were selected from first year BDS and were divided into group 1 and 2 comprising of 27 and 26 students respectively. Group 1 learned anatomy and physiology of ascending tracts through four integrated sessions while group 2 was taught same content through traditional teaching sessions. At the end of sessions, knowledge was assessed and compared through a MCQ based exam. Questionnaire based perceptions were gathered about the integrated sessions from the participants belonging to group 1. Results: The mean score of the students from group 1 (34.8 ± 6.53) was higher than that of group 2 (31.36 ± 5.71) (P<0.05). Most of the students positively perceived this method of teaching and felt that it was more understandable, motivating, interesting and they would prefer this method over traditional teaching. Conclusion: Integrated sessions for anatomy and physiology of ascending tracts enhanced academic performance and were positively perceived by the students.